Kendala Regulasi Kewajiban Pemegang Paten oleh Investor Asing di Indonesia - Fahnizar Dandy Hediyanto; Kholis Raisah; Anggita Doramia Lumbanraja (Notarius, 2021)
AbstractThe Obligations of patent holders based on Article 20 as regulated in Law Number 13 of 2016 concerning patents are still relatively problematic. The factors that hinder the process of patent implementation in Indonesia, both from patent holders and/or from the Indonesian government, are a separate problem for patent holders who are foreign citizens. This study uses a normative juridical method, using secondary data. The results of the study conclude that the Patent Law Number 13 of 2016 creates problems, especially for inventors from abroad. So that the Indonesian Government issued Permenkumham Number 30 of 2019 concerning Procedures for Granting Compulsory Patent Licenses as a solution to this problem through the Ministry of Law and Human Rights, where patent holders can submit applications for postponement of patent implementation to the Minister along with the background for the delay, in the case of patent holders has not been able to apply his patent in Indonesia after the patent application has been approved. Keywords: Obligations of Patent Holder; Patent Regulations; Foreign Investor ABSTRAKKewajiban pemegang paten berdasarkan Pasal 20 sebagaimana diatur pada Undang-Undang Nomor 13 Tahun 2016 tentang Paten masih relatif mengundang permasalahan. Faktor yang menghalangi untuk proses implementasi paten di Indonesia baik yang berasal dari pemegang paten dan/atau dari pemerintah Indonesia, menjadi permasalahan tersendiri bagi pemegang paten yang merupakan Warga Negara Asing. Penelitian ini menggunakan metode yuridis normatif, dengan menggunakan data sekunder. Hasil penelitian menyimpulkan bahwa Undang-Undang Paten Nomor 13 Tahun 2016 menimbulkan permasalahan terutama untuk investor dari luar negeri. Sehingga Pemerintah Indonesia mengeluarkan Permenkumham Nomor 30 Tahun 2019 tentang Tata Cara Pemberian Lisensi-Wajib Paten sebagai solusi atas permasalahan tersebut melalui Kementerian Hukum dan HAM, dimana Pemegang paten dapat menyampaikan permohonan penundaan pelaksanaan paten kepada Menteri beserta latar belakang atas penundaan tersebut, dalam hal pemegang paten belum mampu untuk menerapkan patennya di Indonesia setelah permohonan paten tersebut disetujui. Kata Kunci: Kewajiban Pemegang Paten; Regulasi Paten; Investor Asing